Two-Point Compression Ultrasonography for Lower Extremity Deep Venous Thrombosis in Comparison to Whole-Leg Duplex Ultrasonography - Farkhanda Akhtar Abbasi, Shafia Naeem, Ayesha Anwar,Faisal Mahmood,Umar Liaqat (Journal of Rawalpindi Medical College, 2013)
Background: To determine the validity of 2-point compression ultrasound in the evaluation of DVT in comparison to whole-leg duplex scan. Methods: In this cross-sectional study 2-point compression scan and whole leg duplex scan were performed. In two point compression ultrasound the common femoral at the groin and the popliteal vein down to its branching into the calf deep veins at the popliteal fossa were examined in the transverse phase with a linear probe. In duplex ultrasound all leg veins were imaged continuously along their length in the transverse plane. Vein incompressibility was the diagnostic criteria for two point compression and whole leg duplex scan Results: The mean age was 51.5±16.7 years with 44% males. Out of 50 patients, majority (54%) had positive and 26% had a negative 2-point CUS. Thirty five (70%) had positive and 48% had a negative whole-leg duplex scan. Two-point CUS was correct in 92% cases. Patients with a positive 2-point CUS had a statistically significant probability of having a confirmed DVT on whole-leg duplex scan; p= 0.00, Odds ratio(OR) = 8.095, 95% confidence interval (CI)= 3.303-19.840. The calculated sensitivity, specificity, positive predictive value(PPV) and negative predictive value(NPV) of the 2-point CUS in comparison to whole-leg duplex scan was 97%, 80%, 92% and 92.3% respectively. Conclusion: 2-point compression ultrasound is more accurate as compared to whole-leg strategy for the diagnosis of DVT in symptomatic patients presenting with leg swelling.